Considering gender differences in measuring household food insecurity in northern Ghana. Issue 4 (19th May 2022) - Vercillo, Siera; McCordic, Cameron; Frayne, Bruce
ABSTRACT : This study compares estimates of household food insecurity between men and women living within the same household ( n = 866) to assess whether there is a gender bias in reporting. The main research question is, do household food insecurity scores and prevalence categories differ between male and female spouses within households in the sample? Findings indicate that men's household food insecurity estimates were lower on average at 3.49, than women's estimates at 5.06. There is also a statistically significant decrease in men's estimates when compared to women's. Overall, these findings question the reliability of household-level food insecurity measures that rely on heads of households' estimations by pointing to discrepancies found in this reporting between husbands and wives within the same household. Since this study sampled married women and men within the same household, gender differences found are also more directly attributable to gender than in most other studies that compare male and female-headed households' food insecurity reporting. Though further assessments across other cases are needed, more reliable measures of household food insecurity could include averaging estimates of multiple individuals within households. Qualitative research into the gendered dynamics could also improve sampling and the interpretation of findings from surveys on household-level measures.